2021
DOI: 10.4149/neo_2021_210103n3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic profiling of blood plasma of patients with lung cancer and malignant tumors with metastasis in the lungs showed similar features and promising statistical discrimination against controls

Abstract: Targeting metabolomic pathways is a promising strategy for cancer treatment. Alterations in the metabolomic state have also an epigenetic impact making the metabolomic studies even more interesting. We explored metabolomic changes in blood plasma of patients with primary and secondary lung cancer and tried to explore their origin. We also applied a discrimination algorithm on the data. In the study, blood samples from 132 patients with primary lung cancer, 47 with secondary lung cancer, and 77 subjectively hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…They identified potentially increased pyruvate carboxylase and high proliferation rates of metastatic tumors that could be associated with high utilization of pyruvate, leading to a decrease in the serum pyruvate level. This is in line with another study by Sarlinova et al, which demonstrated significant increases in glucose, citrate, acetate, 3-hydroxybutyrate, and creatinine, and decreases in pyruvate, lactate, alanine, tyrosine, and tryptophan in cancer patients compared with healthy control subjects, posing the potential of NMR plasma metabolomics as a screening tool for lung cancer and showing promising statistical discrimination against healthy controls [42]. The use of 1 H-NMR spectroscopy aids in the identification of serum biomarkers for detecting NSLC at an early stage, distinguishing it from healthy individuals.…”
Section: Nmr Metabolomics In Lung Cancer Researchsupporting
confidence: 90%
“…They identified potentially increased pyruvate carboxylase and high proliferation rates of metastatic tumors that could be associated with high utilization of pyruvate, leading to a decrease in the serum pyruvate level. This is in line with another study by Sarlinova et al, which demonstrated significant increases in glucose, citrate, acetate, 3-hydroxybutyrate, and creatinine, and decreases in pyruvate, lactate, alanine, tyrosine, and tryptophan in cancer patients compared with healthy control subjects, posing the potential of NMR plasma metabolomics as a screening tool for lung cancer and showing promising statistical discrimination against healthy controls [42]. The use of 1 H-NMR spectroscopy aids in the identification of serum biomarkers for detecting NSLC at an early stage, distinguishing it from healthy individuals.…”
Section: Nmr Metabolomics In Lung Cancer Researchsupporting
confidence: 90%
“…Another amino acid that was significantly reduced in the plasma of NSCLC patients was alanine, as previously reported by different authors ( 35 , 40 , 45 ). The decrease of serum alanine concentration in breast cancer patients was reported by Eniu et al ( 46 ).…”
Section: Discussionsupporting
confidence: 78%
“…Metabonomics analysis showed that there was no significant difference in plasma metabolites between primary lung cancer and secondary lung cancer.Compared with the healthy control group, the common characteristics of the lung cancer group were significantly increased glucose, citrate, acetate, 3-hydroxybutyrate, and creatinine levels, and decreased pyruvate, lactic acid, alanine, tyrosine, and tryptophan levels. The differential metabolites mentioned above can be used as auxiliary modes for diagnosing lung cancer 74 .…”
Section: Sample Types Of Lung Cancer Metabolomicsmentioning
confidence: 99%
“…The improvement of various metabolomics databases and the development of machine learning schemes, as well as the continuous improvement of the performance of various detection instruments, may provide more reliable means to accurately and efficiently find differential metabolites. Following untargeted metabolomics analysis, the addition of targeted metabolomics studies can enable further validation of the selected differential metabolites 128 . Of course, differential metabolites are not equal to disease biomarkers, and rigorous medical validation is needed prior to their application in clinical practice.…”
Section: Summary and Prospectsmentioning
confidence: 99%